Numerical investigation of seabed changes of caisson breakwater suspended on piles - Rana N. Zedan; I. M. H. Rashwan; A. S. Koraim; H. Omara (Water Science)
Scouring at coastal structures is a serious issue that threatens structures. Previous research, focused on scour around vertical breakwaters, has shown that scour is mainly brought on by standing waves in front of structures. Scours caused by flow may be the dominating factor for breakwaters, which are composed of caisson breakwater suspended on piles. However, many breakwaters lose their stability and function due to scour. In the present study, a three-dimensional numerical model is developed to investigate modifying the caisson’s cross section for different four scenarios on controlling the scour progress around a semi-immersed caisson suspended on piles under wave action. Also, the consequence of reinforcing the piles by slotted with different heights was examined. The Reynolds-Averaged Navier – Stokes (RANS) equations, coupled with the Renormalization Group (RNG) turbulence model, are formulated to simulate the morphological performance surrounding the caisson breakwater. A numerical contour map was assessed for scour and deposition progress under the breakwater and around the piles. The simulation results are compared to the previous experimental data, showing a satisfactory level of agreement. A significant correlation was observed between the maximum relative hole length around the piles and the dimensionless wave number, particularly as the breakwater draft increased. Furthermore, for a large-spaced pile, the results demonstrated a high level of convergence between the numerical and experimental findings, with a low mean square error. The maximum scour depth decreased by 30% by increasing the base of the barrier by 0.50W as W is the breakwater width from both sides, compared to increasing the base of the barrier by 0.50W from only one side. The attempt to increase the overall width of the breakwater by 0.25W successfully moved scour away from the breakwater and the piles while maintaining its constant value. A minor effect is observed when increasing the caisson’s front wall for different heights in controlling the scour process. The impact of the pile system strengthening with different slotted heights led to changing the scour location from seaward to shoreward.